2015
DOI: 10.5114/pwki.2015.54017
|View full text |Cite
|
Sign up to set email alerts
|

The utility of cardiac magnetic resonance imaging in Kounis syndrome

Abstract: IntroductionCurrent diagnostic measurements used to assess myocardial involvement in Kounis syndrome, such as electrocardiography (ECG), cardiac enzymes, and troponin levels, are relatively insensitive to small but potentially significant functional change. According to our review of the literature, there has been no study using magnetic resonance imaging (MRI) on Kounis syndrome except for one case report.AimTo identify the findings of dynamic contrast-enhanced magnetic resonance imaging (CE-MRI) in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
1
15
0
2
Order By: Relevance
“…There is no need to perform invasive FFR to confirm or exclude the severity of lesions which were qualified based on CMR perfusion. Moreover, CMR offers an overall assessment of the myocardial tissue including myocardial vitality [14]. Our research enhances the results of previous reports confirming the adequacy and consistency of both methods [15].…”
Section: Discussionsupporting
confidence: 84%
“…There is no need to perform invasive FFR to confirm or exclude the severity of lesions which were qualified based on CMR perfusion. Moreover, CMR offers an overall assessment of the myocardial tissue including myocardial vitality [14]. Our research enhances the results of previous reports confirming the adequacy and consistency of both methods [15].…”
Section: Discussionsupporting
confidence: 84%
“…Dynamic cardiac magnetic resonance imaging (MRI) is also a reliable tool for assessing cardiac involvement in Kounis syndrome. Delayed contrast-enhanced images show normal washout in the subendocardial lesion area in patients with Kounis syndrome type I variant [105].…”
Section: Diagnosismentioning
confidence: 99%
“…Keita Goto et al [11] reported that thallium-201 (Tl) single-photon emission CT (SPECT) and 125I-15-(p-iodophenyl)-3-(R,S)-methylpentadecanoic acid (BMIPP) SPECT were conducted in a post-Kounis syndrome patient, and they revealed a local perfusion defect with decreased BMIPP uptake. Aylin Okur et al [12] included 26 patients with known or suspected Kounis syndrome and conducted contrast-enhanced magnetic resonance imaging. The results revealed an early-phase subendocardial contrast defect and local edema in lesion areas in T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%